Multiple Masks: Neoclassicism in Stravinsky's Works on Greek Subjects - Carr, Maureen A. (London, NB University of Nebraska Press, 2002)
In Multiple Masks, Maureen A. Carr studies Igor Stravinsky's creative process for Oedipus Rex, Apollo, Perséphone, and Orpheus through his musical sketches and other documents?scenarios, librettos, correspondence, reviews, and philosophical commentaries, as well as previously uncited sources for Stravinsky's book Poetics of Music. A clear explanation of Stravinsky's compositional techniques within a broad cultural context emerges for each of these four significant works. Carr concludes that Stravinsky used Greek myths as filters for certain poetic ideas and musical techniques that he developed in his earlier works. At the same time the mythological story lines provided him with the objective stance that he was seeking in these neoclassical works
Keywords: Stravinsky, Igor -- 1882-1971; 20th Century (1901-2000); Musical analysis; Musical style; Mythology